2011
DOI: 10.1186/1471-2180-11-15
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary patterns of proteinase activity in attine ant fungus gardens

Abstract: BackgroundAttine ants live in symbiosis with a basidiomycetous fungus that they rear on a substrate of plant material. This indirect herbivory implies that the symbiosis is likely to be nitrogen deprived, so that specific mechanisms may have evolved to enhance protein availability. We therefore hypothesized that fungal proteinase activity may have been under selection for efficiency and that different classes of proteinases might be involved.ResultsWe determined proteinase activity profiles across a wide pH ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…4A). This is consistent with studies showing that both hemicellulases and proteases are produced by this organism (20,50,51) and that activity against these substrates can be consistently detected in whole fungus gardens (52). Moreover, culture-based work has shown that L. gongylophorus can produce enzymes active against a variety of polysaccharides when grown in pure culture (53,54).…”
Section: Discussionsupporting
confidence: 74%
“…4A). This is consistent with studies showing that both hemicellulases and proteases are produced by this organism (20,50,51) and that activity against these substrates can be consistently detected in whole fungus gardens (52). Moreover, culture-based work has shown that L. gongylophorus can produce enzymes active against a variety of polysaccharides when grown in pure culture (53,54).…”
Section: Discussionsupporting
confidence: 74%
“…Protease activity was measured using the Azocasein method (Charney and Tomarelli, 1947) used previously in studies on attine protease activity (Semenova et al, 2011). This method uses azocasein (azo-labeled casein; Sigma-Aldrich).…”
Section: Fungal Enzymatic Activity Assaysmentioning
confidence: 99%
“…In the 1970s, leaf-cutting ant fecal fluid was shown to contain active proteases (Martin, 1970(Martin, , 1974Martin, 1970a, b, 1971) with similar chemical properties as enzymes originating from the fungal symbiont (Boyd and Martin, 1975a, b), and recent work has shown that fungus garden endo-protease activity in evolutionarily derived leaf-cutting ants is much higher than in sister ant lineages that do not use fresh leaves to make their gardens grow (De Fine Licht et al, 2010), activity that could subsequently be assigned to metalloproteases and serine proteases (Semenova et al, 2011).…”
Section: Introductionmentioning
confidence: 99%